2232. Association between Inappropriate Empiric Therapy (IET) and 30-Day Emergency Department/Inpatient (ED/IP) Visits Among Adult Outpatients (OPs) with Complicated Urinary Tract Infections (cUTIs). (15th December 2022) - Lodise, Thomas P; Chen, Lie Hong H; Bruxvoort, Katia J; Wei, Rong; Im, Theresa M; Contreras, Richard; Rodriguez, Mauricio; Friedrich, Larry; Reese, Jennifer; Tartof, Sara Y
Abstract: Background: Deleterious outcomes associated with IET are well documented among hospitalized patients with infections. However, scant data exist on the consequences of IET among adult OPs with cUTIs. This study evaluated the association between receipt of IET and 30-day ED/IP visits among adult OPs with cUTIs. Methods: Retrospective cohort study among Kaiser Permanente Southern California members from 2017-20. Inclusion criteria were age ≥18 years; cUTI diagnosis during an OP visit; positive urine culture with antibiotic (AB) susceptibility results; receipt of AB ±3 days of index urine culture; and not hospitalized on day of OP visit. For OPs with multiple cUTIs, only the index cUTI was considered. IET was defined as failure to receive an AB with in vitro microbiologic activity against all recovered cUTI pathogens ±3 days of culture collection date. Outcomes included all-cause and cUTI-related ED/IP visits ≥3 days to ≤30 days from index culture date. Logistic regression was used to adjust for baseline differences between appropriateness groups. Results: During study period, 25, 980 OPs with cUTIs met study criteria. Mean age was 60 years, majority female (57%), and E. coli (66%) was the most common pathogen. IET was noted in 2656 (10%) of patients. Comparison of baseline characteristics between appropriateness groups is shown in Table . Comparison of 30-day all-cause and cUTI-related ED/IP visits between IET and appropriate empiric therapy (AET) is shown in Figure . In the logistic regression, receipt of IET was associated with an increase odds of 30-day all-cause ED/IP visits (adjusted odds ratio (aOR)= 1.3; 95% CI: 1.2-1.4) and 30-day cUTI-related ED/IP visits (aOR=1.5; 95% CI: 1.4-1.7), respectively. Figure Conclusion: Thirty-day all-cause and cUTI-related ED/IP visits were significantly higher among adult OPs with cUTI who received IET. As culture and susceptibility results are frequently unknown at the time of empiric therapy selection, the findings highlight the critical need to use institution-specific antibiotic resistance risk stratification tools, in tandem with rapid diagnostic tests, to guide empiric antibiotic decisions among OPs with cUTIs as measures to ensure patients receive AET and maximize chances of a successful clinical outcome. Disclosures: Thomas P. Lodise, PharmD, PhD, Spero Therapeutics: Advisor/Consultant Lie Hong H. Chen, DrPH, MSPH, Spero Therapeutics: Grant/Research Support Katia J. Bruxvoort, PhD, MPH, Dynavax: Grant/Research Support|Gilead: Grant/Research Support|Glaxosmithkline: Grant/Research Support|Moderna: Grant/Research Support|Pfizer: Grant/Research Support|Seqirus: Grant/Research Support Rong Wei, MA, Spero Therapeutics: Grant/Research Support|Spero Therapeutics: Grant/Research Support Theresa M. Im, MPH, Spero Therapeutics: Grant/Research Support Richard Contreras, MS, Spero Therapeutics: Grant/Research Support Mauricio Rodriguez, PharmD, MS-HEOR, BCPS, BCCCP, BCIDP, Spero Therapeutics: Employee Larry Friedrich, PharmD, Spero Therapeutics: Employee Jennifer Reese, PharmD, Spero Therapeutics: Employee Sara Y. Tartof, PhD MPH, Pfizer: Grant/Research Support|Spero: Grant/Research Support.